Probiotic has prophylactic effect on spatial memory deficits by modulating gut microbiota characterized by the inhibitory growth of Escherichia coli - Zhang, Jie; He, Zengyang; Liu, Lulu; Li, Huailong; Wang, Tian; Zhu, Xuefeng; Wang, Yanqing; Zhu, Dongliang; Ning, Yong; Xu, Yi (Frontiers in Integrative Neuroscience, 2023)
Background: The aim of this study is to interrogate the prophylactic effect of probiotic on the lead-induced spatial memory impairment, as well as the underlying mechanisms based on gut microbiota. Methods: Rats were exposed postnatally with 100 ppm of lead acetate during lactation (from postnatal day 1 to 21), to establish the memory deficits model. A probiotic bacterium, namely Lacticaseibacillus rhamnosus, was administered by drinking into pregnant rats with dosage of 109 CFU/rat/d till birth. At postnatal week 8 (PNW8), the rats were subjected to Morris water maze and Y-maze test, with fecal samples collected for 16S rRNA sequencing. Besides, inhibitory effect of Lb. rhamnosus on Escherichia coli was carried out in bacterial co-culture. Results: Female rats prenatally exposed by probiotic improved their performances in behavioral test, indicating that probiotic could protect rats from memory deficits caused by postnatal lead exposure. This bioremediation activity varies depending on the intervention paradigm used. As revealed by microbiome analysis, although administered in a distinct period from lead exposure, Lb. rhamnosus further changed the microbial structure disrupted by the lead exposure, suggesting an effective transgenerational intervention. Of note, gut microbiota, represented by Bacteroidota, varied greatly depending on the intervention paradigm as well as developmental stage. The concerted alterations were revealed between some keystone taxa and behavioral abnormality, including lactobacillus and E. coli. To this end, an in vitro co-culture was created to demonstrate that Lb. rhamnosus could inhibit the growth of E. coli with direct contact, which is dependent on the growth condition under study. In addition, in vivo infection of E. coli O157 aggravated the memory dysfunction, which could also be rescued by probiotic colonization. Conclusions: Early probiotic intervention could prevent organisms from the lead-induced memory decline in later life through reprogramming gut microbiota and inhibiting E. coli, providing a promising approach to ameliorate the cognitive damage with environmental origins.